Child Exposure to Intimate Partner Violence and Parent Aggression in Two Generations, United States, 2016-2018 - Shortt, Joann Wu ([Verlag nicht ermittelbar], 2019)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The research purpose of this project was to advance the scientific understanding of children's exposure to family violence and children's adjustment. This research examined the prevalence of child exposure to psychological and physical Intimate Partner Violence (IPV) and parent-to-child aggression (PCA), proximal associations with child externalizing and internalizing behavior, social and scholastic competence in early childhood and adolescence, and the developmental timing and intergenerational transmission of exposure to IPV and PCA related to child externalizing behavior. The study also looked at child effortful control and positive parenting as risk and protective factors theorized to mediate associations between child exposure to family violence and later child adjustment. Secondary analyses were conducted using a prospective multigenerational data set involving community families from lower socioeconomic status backgrounds that comprise the Three Generational Study. The study collection includes 3 SPSS (.sav) files. The zip file includes CEV_3GS4_Cooccur_itemsB_12212018.sav (n= 283; 356 variables), CEV_3GS7_Cooccur_itemsB_12212018.sav (n= 184; 341 variables), CEV_OYS5_Cooccur_itemsC_12212018.sav (n= 206; 368 variables).